The Effectiveness of Implementing Restorative Justice in Resolving Criminal Cases in the Jurisdiction of the Serang Banten Police - Akbar S, Muhammad Aqlizar; Mashdurohatun, Anis (UNISSULA Semarang, 2025)
The application of Restorative Justice as an alternative to resolving criminal cases has been explicitly regulated in the Regulation of the Chief of Police Number 8 of 2021 concerning Handling of Criminal Cases with a Restorative Approach. In the jurisdiction of the Serang Banten Police, this concept is applied to accelerate the case resolution process by prioritizing the restoration of relations between perpetrators, victims, and the community. Restorative Justice is also in line with the principle of protecting Human Rights. This study aims to examine and analyze the effectiveness of the application of Restorative Justice in resolving criminal cases in the jurisdiction of the Serang Banten Police and to examine and analyze the obstacles to the application of Restorative Justice as in resolving criminal cases in the jurisdiction of the Serang Banten Police and its Solutions. The research method used by the researcher is a legal approach in a sociological juridical manner, with descriptive research specifications. The data sources used include primary data obtained through observation and interview processes, as well as secondary data obtained from documents and literature studies. All data are then analyzed qualitatively with the approach of law enforcement theory, restorative justice theory, and restorative justice theory in an Islamic perspective. Based on the results of the study on the effectiveness of the application of restorative justice in resolving criminal cases in the jurisdiction of the Serang Banten Police, the application of restorative justice in the jurisdiction of the Serang Police has not been effective, because not all criminal cases have been resolved through the Restorative Justice approach or outside the formal justice system, based on data from 2022 P21 126 cases RJ 32 cases, 2023 P21 188 cases RJ 50 cases, 2024 P21 137 cases RJ 28 cases. There is no law that specifically regulates Restorative Justice, the application of Restorative Justice at the Banten Police is based on Perpol Number 8 of 2021, PERMA Number 1 of 2024, Law Number 2 of 2002, then Law Number 39 of 1999, the police have the authority to resolve minor cases through penal mediation. The mechanism is through a peace agreement between the perpetrator and the victim. The benefit is a reduced burden of cases in court. Obstacles. Obstacles in the implementation of Restorative Justice in Polres Serang explain five factors (legal factors, enforcement factors, community factors, cultural factors and infrastructure) found, including minimal socialization, limited technical training for officers, and resistance from parties who still adhere to the retributive approach. The solution requires strengthening regulations, increasing human resource capacity, and collaboration between institutions to support the sustainability and optimization of the implementation of Restorative Justice as a whole.